Public Policies for the Development of ICT in the State of Michoacan, Mexico - Molina Martínez, Rubén (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2014)
Information and Communication Technologies are currently one of the most tangible ways to access the Knowledge Society, but their incorporation into government processes and their support to the development of society, depend largely onthe existence of accurate and specific public policies that allow the government to own and implement ICT and to support the rest of society to achieve development. The transformation of society implies a new form of marginalization: the Digital Divide, which is based on whether people have the ability toaccess all the resources of the Knowledge Society. This paper is oriented to present a proposal for the government of Michoacán, to take advantage of Information and Communication Technologies, allowing it to provide a better service to citizens, achieve a proper relationship and linkage between government’s agencies and provide society a real opportunities to participate more in decision-making and governance policies.